Magnetically hard ferrite nanoparticles synthesized through aerogel nanoreactor. (28th August 2020) - Ji, Rui; Shao, Zefan; Li, Zheng; Wang, Jieyu; An, Lu; Guo, Zipeng; Zhou, Chi; Ren, Shenqiang
Abstract: Magnetic ferrite materials have been extensively studied for a range of technological applications, such as magnetic motors, recording media, and millimetre-wave devices. In this context, the nanosized epsilon phase of Fe2 O3 (ϵ-Fe2 O3 ) attracts significant attention due to its high coercive field at room temperature. Here, we report the in-situ aerogel nanoreactor growth of magnetic ϵ-Fe2 O3 nanoparticles, exhibiting a coercive field (Hc ) of 4000 Oe. We show that the control of nanoreactor plays an important role in the growth of ϵ-Fe2 O3 nanoparticles. The findings provide a versatile reaction pathway for the growth of magnetically hard ferrite nanoparticles.